(untitled) (Journal of Invasive and Clinical Cardiology, 2023)
Background: Bed side ophthalmoscopic examination is a simple measure of diagnosis of diabetic retinopathy and has been shown to be a predictor of poor outcome in various cardiovascular conditions including coronary artery disease (CAD). Retinopathy lesions are fairly common findings in clinic settings and may predict risk of coronary heart disease (CHD). The present study was intended to find the relationship between diabetic retinopathy with the severity of coronary artery disease in patients with NSTEMI. Methods: This cross-sectional observational study was conducted in the Department of cardiology, National Institute of Cardiovascular Diseases and Hospital (NICVD), Dhaka, Bangladesh, from March 2019 to August 2020. A total of one hundred twenty DM with NSTEMI patients undergoing coronary angiogram and also fundoscopic examination with fundal photography during the index hospitalization were included in this study. Study subjects were divided into two groups on the basis of diabetic retinopathy (Group-I: NSTEMI with diabetic retinopathy ; Group- II: NSTEMI without diabetic retinopathy). Severity of coronary artery disease was determined by Gensini score and correlation between diabetic retinopathy and Gensini score was assessed. Results: Gensini score was significantly higher in patients with diabetic retinopathy than that in patients without diabetic retinopathy (62.2±27.7 vs. 43.3±25.3,p<0.001).Gensini score increased with increasing severity of diabetic retinopathy(P <0.001).The risk of having severe CAD in patient with diabetic retinopathy was 13.03 (95% CI =2.410-70.419) (P<0.003).A significant correlation between diabetic retinopathy and Gensini score was noted (p value <0.001) Conclusion: It may be concluded that Presence and severity of diabetic retinopathy is associated with angiographically severe coronary artery disease in patient with non-ST elevation myocardial infarction (NSTEMI) and it may be considered as an independent predictor of severity of CAD.As is a bed side assessment ,so before performing coronary angiography ,it appears to be additive for risk stratification. J Inv Clin Cardiol 2023; 5(1): 7-13